Study and application of information system of ecological rebuilding in limestone mountains - WANG Shen-fa; HU Zhen-zhen; YU Jian-qiang; CHEN He-ping (浙江大学学报. 农业与生命科学版)
Based on the study of soil classification, basic category of land, tria1 of ecological rebuilding and planning of ecological economy, the information system of ecological rebuilding at large scale in the area of limestone mountains was studied. The results of its application showed that the system has function of analyzing ecological status quo, classifying the land resource at basic category and evaluating the land suitability. Characterized by its scientific and practicable capability, the system had surpassed the traditional plannings and it could offer a new technique to ecological planning of limestone mountains in the southwest of China.